Specific Profile of Tau Isoforms in Argyrophylic Grain Disease - Alberto Rábano; Raquel Cuadros; Miguel Calero; Félix Hernández; Jesús Avila (Journal of Experimental Neuroscience, 2013)
Argyrophylic grain disease (AGD) is a neurodegenerative condition that has been classified among the sporadic tauopathies. Entities in this group present intracellular aggregates of hyperphosphorylated tau, giving rise to characteristic neuronal and glial inclusions. In different tauopathies, the proportion of several tau isoforms present in the aggregates shows specific patterns. AGD has been tentatively classified in the 4R group (predominance of 4R tau isoforms) together with progressive supranuclear palsy and corticobasal degeneration. Pick's disease is included in the 3R group (predominance of 3R isoforms), whereas tau pathology of Alzheimer's disease represents and intermediate group (3 or 4 repeats [3R plus 4R, respectively] isoforms). In this work, we have analyzed tau present in aggregates isolated from brain samples of patients with argyrophylic grain disease. Our results indicate that the main tau isoform present in aggregates obtained from patients with AGD is a hyperphosphorylated isoform containing exons 2 and 10 but lacking exon 3.